Oral Senescence: From Molecular Biology to Clinical Research - Parkinson, Eric Kenneth; Prime, Stephen Stewart (Frontiers in Dental Medicine, 2022)
Classical cellular senescence is defined as an irreversible cell cycle arrest that is distinct from quiescence, terminal differentiation and apoptosis. Classical cellular senescence occurs following multiple rounds of cell division (replicative senescence) or in response to cellular stresses such as ionizing radiation, signaling imbalances and oxidative damage (stress-induced premature senescence). It also occurs in development and following cancer therapy. However, senescence is a double-edged sword because it operates as a suppressor of malignancy but also, can promote wound repair and stem cell activation. Even very small numbers of senescent cells can be deleterious and there is evidence that senescent cells are instrumental in a number of oral pathologies including cancer, oral submucous fibrosis and the side effects of cancer therapy. Many of these effects are dependent on the secretion of an array of diverse proteins known as the senescence-associated secretory phenotype. Here, we discuss biological mechanisms of senescence and we review the current approaches to target senescent cells therapeutically, including senostatics and senolytics which are entering clinical trials.